FMF is not always "fever": from clinical presentation to "treat to target" - Maria Cristina Maggio; Giovanni Corsello (BMC, 2020)
Abstract Familial Mediterranean Fever, a monogenic autoinflammatory disease secondary to MEFV gene mutations in the chromosome 16p13, is characterized by recurrent self-limiting attacks of fever, arthritis, aphthous changes in lips and/or oral mucosa, erythema, serositis. It is caused by dysregulation of the inflammasome, a complex intracellular multiprotein structure, commanding the overproduction of interleukin 1. Familial Mediterranean Fever can be associated with other multifactorial autoinflammatory diseases, as vasculitis and Behçet disease. Symptoms frequently start before 20 years of age and are characterized by a more severe phenotype in patients who begin earlier. Attacks consist of fever, serositis, arthritis and high levels of inflammatory reactants: C-reactive protein, erythrocyte sedimentation rate, serum amyloid A associated with leucocytosis and neutrophilia. The symptom-free intervals are of different length. The attacks of Familial Mediterranean Fever can have a trigger, as infections, stress, menses, exposure to cold, fat-rich food, drugs. The diagnosis needs a clinical definition of the disease and a genetic confirmation. An accurate differential diagnosis is mandatory to exclude infective agents, autoimmune diseases, etc. In many patients there is no genetic confirmation of the disease; furthermore, some subjects with the relieve of MEFV mutations, show a phenotype not in line with the diagnosis of Familial Mediterranean Fever. For these reasons, diagnostic criteria were developed, as Tel Hashomer Hospital criteria, the "Turkish FMF Paediatric criteria", the "clinical classification criteria for autoinflammatory periodic fevers" formulated by PRINTO. The goals of the treatment are: prevention of attacks recurrence, normalization of inflammatory markers, control of subclinical inflammation in attacks-free intervals and prevention of medium and long-term complications, as amyloidosis. Colchicine is the first step in the treatment; biological drugs are effective in non-responder patients. The goal of this paper is to give a wide and broad review to general paediatricians on Familial Mediterranean Fever, with the relative diagnostic, clinical and therapeutic aspects.